Impacto de la integración vertical de distribuidores de combustibles: servicentro Olaya-Boyacá (2017)
The Servicentro Olaya Service Station is a retail establishment dedicated to the retail distribution of petroleum-based liquid fuels. It is located in the urban area of ​​the city of Sogamoso department of Boyacá. Because in recent years, the company has experienced significant changes in economic behavior, especially from the implementation of new business models established within the framework of national regulation; requires under this scheme, maintain commercial activity, continue to be competitive, economically profitable, and even surpass projected economic growth expectations, an aspect that has been altered by different dynamics, coinciding with the application of the vertical integration model.